The impact of glucose control index on erectile hardness score among type 2 diabetes mellitus patients - Sakti Brodjonegoro; Andy Zulfiqqar; Franky Renato Anthonius; Amanda Cyko; Pandu Ishaq Nandana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
The prevalence of erectile dysfunction (ED) was reported to vary from 37.5 to52% in men above 40. Type 2 diabetes mellitus (T2DM) maycause the nervesand blood vessels damages that worsened the ED. This study aimed to evaluatethe correlation between the glucose control index and the erection hardnessscore (EHS) among T2DM patients. The cross-sectional observational studywas conducted in two district hospitals i.e. Manambai Abdulkadir DistrictHospital, Sumbawa, and Dompu District Hospital, Dompu, West Nusa Tenggara,Indonesia. Forty-five patients with T2DM were involved in this study. Data werecollected using structural questioners during the period from June 1st to August1st, 2017 and were analyzed using SPSS 24.0. Pearson correlation and logisticregression analysis were used to determine the odds ratio (OR). Among 45patients having age 57.38± 7.22 years involved in this study, 38 (84.4%) patientshad ED, 26 (57.8%) uncontrolled DM, 5 (11.1%) congestive heart failure (CHF),4 (8.9%) chronic kidney diseases (CKD), and 7 (15.6%) neuropathy diabetic.A strong correlation between random glucose level and IIEF-5 score (r=0.91;p=0.01) was observed. The overall odds ratio of ED in this study was 4.3 (95%CI: 0.73 to 25.1) for uncontrolled DM, 2.5 (95% CI: 0.1 to 51.1) for CHF, 2 (95%CI: 0.01 to 41.6) for CKD, and 1.2 (95% CI: 0.1 to 11.5) for neuropathy diabetics.In conclusion, there is a strong correlation between random glucose level,duration of diagnosed DM and EHS. Active screening is recommended for thispopulation.